Penerapan jaringan syaraf tiruan untuk menentukan elemen desain kemasan Numany rempeyek berbasis kansei engineering - Novi Purnama Sari; Vita Anggraini Akkili; Muryeti Muryeti (AGROINTEK, 2024)
In developing packaging, MSME Numany Rempeyek must find out what kind of packaging consumers want. Based on the survey results, 96.8% of respondents stated that the packaging used was not appropriate, as if the packaging was a bit difficult to distribute because the product was easily destroyed, and the packaging was not good in terms of features. and design. This research aims to identify design elements for peanut brittle products based on the concepts obtained. Kansei Engineering is used in packaging development because it can describe consumer desires through their emotions so that it can be customized. The K-Means and Artificial Neural Network methods are used to support the application of Kansei Engineering. The process of determining the concept uses K-Means while the Artificial Neural Network method is used to identify design elements. The research results show two concept clusters, namely "Modern" and "Practical". Meanwhile, the results of the "Modern" concept design elements consist of multilayers (X1.2), center seal (X2.7), sealer (X3.1), modern (X4.1), window only or others (X5.2), illustration (X6.2), black only or combination (X7.2). On the other hand, the "Practical" concept obtains design elements in the form of plastic (X1.1), gusset (X2.4), zip-lock (X3.4), natural (X4.6), tear notch only or others (X5. 3 ), photo (X6.1), brown only or combination (X7.3). This research can produce new packaging designs that are obtained quantitatively to minimize uncertainty and subjectivity in the packaging design process. Kansei Engineering has proven effective in designing packaging based on consumer preferences.